Results of Endoscopic and Surgical Fistula Treatment in Esophagointestinal Anastomosis After Gastrectomy. Issue 4 (August 2016) - Miłek, Tomasz; Myrcha, Piotr; Ciostek, Piotr
Abstract : Introduction: Intestinal fistulas occur in 4% to 8% of cases of upper gastrointestinal tract surgery. Until now, this type of surgery has been the standard for treating fistulas in esophagointestinal anastomosis. The use of stents and hemoclips is still controversial, but an increasing number of publications have been presenting good results with this type of treatment. Objective: The objective of the study was to investigate the outcome of endoscopic and surgical treatment of fistulas in esophagointestinal anastomosis after gastrectomy. Materials and Methods: Fistulas in esophagointestinal anastomoses were observed in 23 patients (4.8%) over an 18-year period. The indications for endoscopic treatment were small (<50 mL/d) and large (>50 mL/d) fistulas in patients with no symptoms of peritonitis or abscess, who were treated with implantation of a covered stent. Surgical intervention was carried out for large fistulas that resulted in peritonitis and complicated gangrene of margins and/or abscesses. Results: Four subjects were treated endoscopically with hemoclips, resulting in 50% technical and clinical success. We implanted stents in 12 patients. Technical success was achieved in all patients; yet, permanent closure of the fistula was reported in 8 subjects (66%). Thirty-three percent of patients were operated upon for fistulas. We reported 4 deaths in this group. Conclusions: The use of hemoclips in the treatment of small fistulas and of self-expandable covered stents in the treatment of medium and large fistulas is an effective method that shortens the hospitalization period and accelerates the introduction of oral nutrition while reducing the number of fatal complications.